GEODYNAMICS OF THREE CONTRASTING TYPES OF OCEANIC MAGMATISM AND THEIR REFLECTION IN THE DATA OF SEISMIC TOMOGRAPHY - Dmitriev L.V.; Sokolov S.Yu. (My University, 2003)
Based on the data of geology, petrology, and geophysics, three discrete geodynamic environments were distinguished in modern oceans, which give rise to the formation of the following types of magmatism and corresponding basalt associations: (1) spreading association (SA) of mid-ocean ridges (MOR); (2) plume association (PA) of MOR; and (3) intraplate magmatism (IM) of islands and seamounts. The optimal P-T conditions of primary melt segregation from mantle sources were estimated for each type of magmatism on the basis of experimental and theoretical modeling. The different lengths of the adiabatic paths of mantle ascent before solidus intersection and formation of magmatic melts of each type suggest that they were formed under contrasting geodynamic conditions. The analysis of data on the distribution of the three main types of magmatism in the ocean and their relationships to tectonics, the character of the gravity field, and tomographic models allowed us to draw the following conclusions. SA is formed through passive mantle upwelling from a depth of about 200 km in correspondence with spreading rate. The least productive SA magmatism is localized in the areas with a cold rigid lithosphere. The formation of PA is connected with active mantle upwelling from depths between 400 and 1000 km in a limited space independent of spreading rate. An increase in spreading rate results in the mixing of SA and PA. IM is related to mantle jets arriving from the lower mantle or the core-mantle boundary. In addition to the IM that traces plate motion, IM was distinguished for the first time that is characterized by a fixed position relative to the deep mantle source (Canary and Cape Verde islands).